KiwiSaver: An Initial Evaluation of the Impact on Retirement Saving - David Law; Lisa Meehan; Grant M Scobie (New Zealand Government, The Treasury, 2011)
KiwiSaver is a voluntary savings scheme aimed at increasing the retirement wealth of a target population. A critical element shaping the success of KiwiSaver is the extent to which individuals participate in the scheme, given its voluntary nature; and, having chosen to participate, the extent to which their attitudes and practices toward savings have been modified by their participation. This paper presents the results of an initial evaluation to assess individuals' saving behaviour following the introduction of the KiwiSaver scheme. It is based on the findings of a national survey conducted in 2010. We find that members adjust their savings portfolio such that only about one third of the contributions they make to their KiwiSaver account represents additional savings. Further, only 22% of respondents report that their expected retirement income would not be sufficient to meet basic living costs. Critically, regression analysis finds no relationship between KiwiSaver membership and any shortfall or excess in respondents' expected retirement income relative to either the amount needed to meet basic needs in retirement or to be comfortable. Consequently, examination of standard measures of programme efficacy such as target effectiveness and leakage suggests that KiwiSaver has been only modestly successful in reaching the target population and that leakage to the non-target population was high. This implies that the ongoing cost of the scheme per target member could exceed 13,000 per year. Finally, recognising that KiwiSaver may have had broader objectives not explicitly stated in the Act, the scheme's possible effect on national saving was examined. In the long run the effect on net national saving appears marginal at best.
Keywords: E21; D10; D91; 330; KiwiSaver; New Zealand; Saving; Retirement; Additionality; Private Altersvorsorge; Sparen; Intertemporale Entscheidung; Haushaltseinkommen; Privater Haushalt; Neuseeland